Vanishing Carleson measures and power compact weighted composition operators - Sharma, A.; Sharma, A. K.; Mursaleen, M. (Methods of Functional Analysis and Topology, 2022)
In this paper, we characterize Carleson measure and vanishing Carleson measure on Bergman spaces with admissible weights in terms of t-Berezin transform and averaging function as key tools. As an application of the main results of this paper, we characterize power bounded and power compact weighted composition operators on Bergman spaces with admissible weights. Надано характеризацію міри Карлесона і міри Карлесона, що прямує до нуля, на просторах Бергмана з допустимими вагами в термінах t-перетворення Березіна та функцією усереднення в якості ключових інструментів. Як застосування основних результатів цієї роботи надано характеризацію степенево обмежених та степенево компактних зважених операторів композиції на просторах Бергмана з допустимими вагами.